2005
DOI: 10.1128/cmr.18.3.465-483.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Escherichia coli in Developing Countries: Epidemiology, Microbiology, Clinical Features, Treatment, and Prevention

Abstract: ETEC is an underrecognized but extremely important cause of diarrhea in the developing world where there is inadequate clean water and poor sanitation. It is the most frequent bacterial cause of diarrhea in children and adults living in these areas and also the most common cause of traveler's diarrhea. ETEC diarrhea is most frequently seen in children, suggesting that a protective immune response occurs with age. The pathogenesis of ETEC-induced diarrhea is similar to that of cholera and includes the productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
808
8
31

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 834 publications
(896 citation statements)
references
References 198 publications
(190 reference statements)
35
808
8
31
Order By: Relevance
“…26 Moreover, in NOD-DQ8 mice the colonization with E. coli ENT CAI:5 isolated from one CD patient increased the sensitivity to gluten-induced immunopathology and suggested that this could be a contributing factor to the disease. 18 The ETEC type is a major cause of diarrhoea, 40 , 41 but it has also been detected in asymptomatic subjects acting as carriers, 42-44 who would presumably have an increased risk of developing gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, in NOD-DQ8 mice the colonization with E. coli ENT CAI:5 isolated from one CD patient increased the sensitivity to gluten-induced immunopathology and suggested that this could be a contributing factor to the disease. 18 The ETEC type is a major cause of diarrhoea, 40 , 41 but it has also been detected in asymptomatic subjects acting as carriers, 42-44 who would presumably have an increased risk of developing gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Katouli et al showed that ST-only with a 78% rate was the most frequent toxin type followed by LT-only (14%) and LTST (8%) [19]. Dominance of the ST-expressing ETEC has been documented in Egypt, Bangladesh, and Tunisia [11,20,21]. However, a recent study conducted in Bangladesh concluded that ETEC strains have shifted from ST-producers to significantly more LTproducing strains similar to those observed in Latin American countries, such as Mexico, Peru, and Argentina, which have shown a high prevalence of LT-producing ETEC [22,11,23].…”
Section: Discussionmentioning
confidence: 99%
“…Dominance of the ST-expressing ETEC has been documented in Egypt, Bangladesh, and Tunisia [11,20,21]. However, a recent study conducted in Bangladesh concluded that ETEC strains have shifted from ST-producers to significantly more LTproducing strains similar to those observed in Latin American countries, such as Mexico, Peru, and Argentina, which have shown a high prevalence of LT-producing ETEC [22,11,23]. The results of this study also showed the predominance of the STproducing strains in the 1988 isolates, but a significant increase in the detection rate of the LTproducers was observed among the 1998 ETEC isolates, and those previously reported [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations